The Influence of Digital Banking Product And Service Innovation on Customer Loyalty Mediated by Customer Satisfaction at Hana Bank Lippo Cikarang - Ratnasari Ratnasari; Adibah Yahya; Susan Kustiwan (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
The development of banking today has undergone a significant transformation over the past few decades, driven by technological advancements, changes in consumer behavior, and increasingly stringent regulations. Banking is one of the crucial sectors in the modern economy. The purpose of this study is to examine the influence of of digital banking product and service innovation on customer loyalty, customer satisfaction at hana bank lippo cikarang. The research method used is a quantitative method processed using smartpls 3.0. the results of this research are